The role of organisational concern for workplace fairness in the choice of a performance measurement system - Lau, James; Martin-Sardesai, A. (Academic Press, 2012)
Prior studies linking performance management systems (PMS) and organisational justice have examined how PMS influence procedural fairness. Our investigation differs from these studies. First, it examines fairness as an antecedent (instead of as a consequence) of the choice of PMS. Second, instead of conceptualising organisational fairness as procedural fairness, it relies on the impression management interpretation of organisational fairness. Hence, the study investigates how the need of senior managers to cultivate an impression of being fair is related to the choice of PMS systems and employee outcomes. Based on a sample of 276 employees, the results indicate that the need of senior management to cultivate an impression of being fair is associated with employee performance. They also indicate that a substantial component of these effects is indirect through the choice of comprehensive performance measures (CPM) and employee job satisfaction. These findings highlight the importance of organisational concern for workplace fairness as an antecedent of choice of CPM. From a theoretical perspective, the adoption of the impression management interpretation of organisational fairness contributes by providing new insights into the relationship between fairness and choice of PMS from a perspective that is different from those used in prior management accounting research.